PENGARUH PRICE EARNING RATIO, BOOK VALUE, PRICE TO BOOK VALUE, EARNING PER SHARE, RETURN ON INVESTMENT DAN CURRENT RATIO TERHADAP HARGA SAHAM PADA SEKTOR PERTAMBANGAN DI BURSA EFEK INDONESIA - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2020)
This study aims to examine the effect of Price Earning Ratio, Book Value, Price to Book Value, Earning Per Share, Return On Investment and Current Ratio on stock prices in mining companies on the Indonesia Stock Exchange. Data collection methods used in this research are documentation and literature study methods. The data used are in the form of annual financial reports, namely 2015 and 2016, the data source is from the Indonesia Stock Exchange / idx. The type of data used is secondary data obtained through the capital market directory issued by the IDX in 2015-2016. Data processing in this study was carried out using multiple linear regression models processed with the SPSS 16.0 for windows program. To analyze the effect of Price Earning Ratio, Book Value, Price to Book Value, Earning Per Share, Return On Investment and Current Ratio.